Experimental study on the seismic performance of a fully assembled column base node with a replaceable energy-consuming joint. (1st June 2023) - Wang, Zongbin; Kang, Qi; Ye, Yanxia
Abstract: To enhance the post-earthquake rehabilitation of the structure and achieve the ability of damage concentration, a brand-new fully prefabricated reinforced concrete column base joint composed of a replaceable energy-consuming joint (RECJ) was introduced in this study. Three prefabricated column specimens joined by RECJ and one monolithic column comparative specimen were both subjected to quasi-static testing. Each specimen's properties, such as failure mechanisms, hysteresis and skeleton curve characteristics, stiffness degradation, bearing capacity, ductility, energy dissipation capacity, and stresses on connecting plates and reinforcements in the column, were examined. The findings demonstrated that the connecting plate of the RECJ was mostly to blame for the damage and failure of the bottom column in the frame, and other components of the specimen typically kept their elastic capacities. The RECJ, whose hysteresis curve was full-shuttle shaped, had much better stiffness degradation, ductility, and energy dissipation than the monolithic comparative column. In terms of overall performance and seismic performance, the specimen with the longer tenon length outperformed the one with the shorter length. The RECJ column's initial stiffness and bearing capacity were the same as those of the monolithic column. In terms of energy dissipation and ductility, strip plate connections outperformed rectangular plate connections, and both connections' bearing capacities were almost similar. Based on an investigation of the RECJ's operating mechanism, the simplified moment-drift model and mechanical model of the RECJ were developed. The rotational stiffness equation was developed. The calculations and the experiments agreed well. It could serve as a guide for creating this type of connection. Highlights: This study proposed a new fully assembled reinforced concrete column base node with a replaceable energy-consuming joint (RECJ). The joint's seismic behavior and failure mechanism were investigated using quasi-static tests. The length of tenon is a main impact factor. The strip plate connection has the advantages of easy installation.